Effect of a voice recognition system on pediatric outpatient medication errors at a tertiary healthcare facility in Kenya. (September 2018) - Migowa, Angela N.; Macharia, William M.; Samia, Pauline; Tole, John; Keter, Alfred K.
Background: Medication-related errors account for one out of every 131 outpatient deaths, and one out of 854 inpatient deaths. The risk is threefold greater in the pediatric population. In sub-Saharan Africa, research on medication-related errors has been obscured by other health priorities and poor recognition of harm attributable to such errors. Our primary objective was to assess the effect of introduction of a voice recognition system (VRS) on the prevalence of medication errors. The secondary objective was to describe characteristics of observed medication errors and determine acceptability of VRS by clinical service providers. Methods: This was a before–after intervention study carried out in a Pediatric Accident and Emergency Department of a private not-for-profit tertiary referral hospital in Kenya. Results: A total of 1196 handwritten prescription records were examined in the pre-VRS phase and 501 in the VRS phase. In the pre-VRS phase, 74.3% of the prescriptions (889 of 1196) had identifiable errors compared with 65.7% in the VRS phase (329 of 501). More than half (58%) of participating clinical service providers expressed preference for VRS prescriptions compared with handwritten prescriptions. Conclusions: VRS reduces medication prescription errors with the greatest effect noted in reduction of incorrect medication dosages. More studies are needed to explore whether more training, user experience and software enhancement would minimize medication errors further. VRS technology is acceptable to physicians and pharmacists at a tertiary care hospital in Kenya.